Performance of Agricultural Extension Services (BPP) in Enhancing Rice Production in North Sumatra, Indonesia - Riris Nadia Syafrilia Gurning; Sakral Hasby Puarada; Wildani Lubis; Nurhajijah Nurhajijah (Universitas Muhammadiyah Malang, 2023)
Indonesia has experienced an increase in national population, the Government is targeting rice production of 54.50 million tons in 2023. North Sumatra Province has the largest rice production on the island of Sumatra, 2,088,584 tons. The effectiveness of the Agricultural Extension Service (BPP) in Percut Sei Tuan is of concern to researchers. This research method uses a differential semantic measurement scale or attitude scale to analyze performance data. The number of samples determined in the research was 10 farmers per village so that the number of samples from all villages was 30 rice farmers with 5-point rating scale and the choices